Tratados Bilaterais de Investimentos (TBIs): Conceitos, potenciais impactos e tendências futuras - Ignácio Tavares de Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The Bilateral Investment Treats (BITs) are a set of rules that regulate private foreign investment from one country to another. The BITs aim to provide desirable security to foreign investors in order to stimulate the inflow of Foreign Direct Investment (FDI). This study reviews a series of empirical and theoretical papers that analyze the effect of BITs on FDI. According to the literature on the subject, there is no consensus on the sign and magnitude of the impact of BITs on FDI. There are evidences suggesting a positive effect, lack of effect and even indicating negative impacts on FDI from BIT. However, more detailed studies do suggest that the TBI may have a positive effect on FDI, but conditional on the country's institutional quality, differences in dispute settlement mechanisms and if the destination country of the investment has not received investor complaints for resolving investor-state disputes. Future trends for TBIs clarify terms such as "indirect expropriation", try new ways to resolve potential disputes without the need to resort to international courts, and seek to avoid making concessions that conflict with domestic policy objectives aiming sustainable development.
Keywords: F21; F53; 330; investment treaties; direct foreign investment